2022
DOI: 10.3389/fsufs.2022.837628
|View full text |Cite
|
Sign up to set email alerts
|

LatitudeTM Oil as a Sustainable Alternative to Dietary Fish Oil in Rainbow Trout (Oncorhynchus mykiss): Effects on Filet Fatty Acid Profiles, Intestinal Histology, and Plasma Biochemistry

Abstract: The aim of this study was to evaluate the effects of Latitude™ oil (transgenic canola) fed to rainbow trout, Oncorhynchus mykiss, for 52 weeks on growth performance, non-specific immune responses, histology, and filet omega-3 fatty acid content. Latitude™ oil (LO) has high lipid digestibility (93%), and contains omega-3 fatty acids eicosapentaenoic acid (EPA, C20:5n-3), docosapentaenoic acid (DPA, C22:5n-3), and docosahexaenoic acid (DHA, C22:6n-3). Three isonitrogenous (49%), isolipidic (20%) and isocaloric (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 55 publications
0
3
0
Order By: Relevance
“…Furthermore, total n‐3 LC‐PUFA content of terrestrial oil blend‐fed fish fillets also meets the recommended dietary consumption level of total n‐3 LC‐PUFA for heart health and human well‐being, albeit in small fish. In another recent, study, Hong et al 217 showed that Latitude™ oil inclusion at 8% or 16%, substituting FO and poultry fat improves fish growth, yields higher filet n‐3 LC‐PUFA content, and creates a viable source of lipid in the diets of rainbow trout. All the above research findings substantiate that the novel sources of EPA and DHA have the potential to increase n‐3 LC‐PUFA levels in salmonids and other farmed fish species with no major adverse effects on their growth, feed utilization efficiency, and health performance.…”
Section: General Classification Of Fufa Used In Aquafeeds: An Overvie...mentioning
confidence: 99%
“…Furthermore, total n‐3 LC‐PUFA content of terrestrial oil blend‐fed fish fillets also meets the recommended dietary consumption level of total n‐3 LC‐PUFA for heart health and human well‐being, albeit in small fish. In another recent, study, Hong et al 217 showed that Latitude™ oil inclusion at 8% or 16%, substituting FO and poultry fat improves fish growth, yields higher filet n‐3 LC‐PUFA content, and creates a viable source of lipid in the diets of rainbow trout. All the above research findings substantiate that the novel sources of EPA and DHA have the potential to increase n‐3 LC‐PUFA levels in salmonids and other farmed fish species with no major adverse effects on their growth, feed utilization efficiency, and health performance.…”
Section: General Classification Of Fufa Used In Aquafeeds: An Overvie...mentioning
confidence: 99%
“…In addition to the benefits that the use of these oils can have for consumers, the use of vegetable oils rich in omega-3 LC-PUFA can also have added benefits for the fish such as reduced liver fat infiltration and hepatocyte area relative to fish fed feeds containing wildtype Camelina [35]. Perhaps, most importantly to note is that none of the trials performed to date have reported any adverse effect in fish fed these novel oils thus demonstrating the potential for the exploitation of this key raw material [27][28][29][30][31][32][33][34][35][36].…”
Section: Cropmentioning
confidence: 99%
“…7%), has a considerably higher ω6:ω3 ratio than ω3 canola oil. Evaluation of Latitude alone or in combination with other oils in feed formulations for farmed shrimp (Litopenaeus vannamei; Gia Vo et al, 2021) and rainbow trout (Oncorhynchus mykiss; Hossain et al 2021, Hong et al 2022 suggests that this oil supports shrimp and salmonid growth with no harmful effects.…”
Section: Brassica Napus (Canola)mentioning
confidence: 99%